Introduction - Erlacher, Esdra (Romanitas - Revista de Estudos Grecolatinos, 2026)
It was our aim, in this dossier, to examine the role played by sophists, philosophers, and rhetores in Antiquity, highlighting their functions, discursive strategies, theoretical disputes, social interests, and other issues related to the activities of these individuals. Drawing on an interdisciplinary perspective that brings together History, Philosophy, Literature, and Anthropology, and based on a highly diverse body of sources, the contributors to this issue set out to understand the actions of a range of individuals or groups in the ancient world who, through their literary and discursive expressions, reinforced or mitigated identities, positions, or projects of power. The texts the reader will encounter in the following pages also constitute a valuable body of material for understanding the circulation, production, and dissemination of knowledge in the ancient Mediterranean.
Keywords: Ancient World; Philosophers; Rhetors; Sophists